Non-Specific Immune Response and Growth Performance of Clarias gariepinus (Burchell, 1822) Feeded with Moringa oleifera Leaf Flour Suplementation (Lamk, 1785) - Nainggolan, Tio Naomi; Harpeni, Esti; Santoso, Limin (Jurnal Perikanan dan Kelautan, 2021)
Sangkuriang catfish (Clarias gariepinus) is a cultivated species favored by Indonesian and has great potential for development. However, the obstacle to the success of catfish cultivation is a disease. One alternative to overcome this problem is by giving immunostimulants from natural ingredients. The purpose of this study was to test the effectiveness of feeding with moringa leaf powder on non-specific immunity and growth performance of sangkuriang catfish. The study used a completely randomized design (CRD) with 4 treatments (100% commercial feed, commercial feed with 1.5% Moringa leaf supplementation, commercial feed with 3% Moringa leaf supplementation, and commercial feed with Moringa leaf supplementation 4.5%, and 3 replications. The results showed that the commercial feed with 4.5% moringa leaf supplementation gave the best results for total erythrocytes of 5.97x104 cells/mm3 and MCV of 92.10 fl, and increased the absolute weight growth of 46.42 g. However, it did not show a significant effect on total erythrocytes, hemoglobin, hematocrit, MCHC, MCH, MCV, total leukocytes, leukocyte differentials, phagocytic activity, phagocytosis index, absolute weight growth survival rate, and the value of the feed convention ratio (FCR).